Tinjauan Yuridis terhadap Kedudukan Fintech Yang Tidak Terdaftar di Otoritas Jasa Keuangan - Muldri Pudamo James Pasaribu (Universitas Medan Area, 2021)
This study aims to, firstly, find out the legal standing of Fintech that is not registered with the Financial Services Authority; Second, to find out the efforts of the Financial Services Authority in dealing with unregistered Fintech. The normative research method used to obtain complete data as the basis for writing scientific papers. Fintech or Financial Technology is a revolutionary business concept that combines the financial business with the development of modern technology and is part of the Industrial Revolution 4.0. Generally, Fintech are companies engaged in financial services that maximize the use of technology to facilitate users of financial services. With the issuance of Financial Services Authority Regulation Number 77/POJK.01/2016 concerning Information Technology-Based Lending and Borrowing Services, which regulates Fintech's obligations to comply with applicable regulations including registration and processing of Financial Services Authority permits